NONALCOHOLIC FATTY LIVER DISEASE AND ALBUMINURIA : A SYSTEMATIC REVIEW - Rizky Taufika, Amandha; Niamullah, Alvita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Non-alcoholic fatty liver disease (NAFLD) is associated with the dysregulation of multiple metabolic and inflammatory pathways. These can lead to extrahepatic disorders involving the kidney, a vulnerable organ responsible for extra-renal complications. Evaluating the association between NAFLD and low-grade albuminuria as a renal complication would be helpful to better understand the pathophysiology and extra-hepatic complications of NAFLD.The aim: This study aims to show incidence, correlation of nonalcoholic fatty liver disease and albuminuria Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: Non-alcoholic fatty liver disease (NAFLD) is associated with the dysregulation of multiple metabolic and inflammatory pathways. These can lead to extrahepatic disorders involving the kidney, a vulnerable organ responsible for extra-renal complications. Evaluating the association between NAFLD and low-grade albuminuria as a renal complication would be helpful to better understand the pathophysiology and extra-hepatic complications of NAFLD.Conclusion: Understanding the incidence, correlation of nonalcoholic fatty liver disease and allbuminuria